Effects of Ultrasound Processing on Physicochemical Parameters, Antioxidants, and Color Quality of Bayberry Juice - Xiamin Cao; Chunfang Cai; Yongling Wang; Xiaojian Zheng (Journal of Food Quality)
Effects of ultrasound on physicochemical parameters, ascorbic acid, anthocyanins, polymeric color (PC), 5-hydroxymethylfurfural (HMF), browning degree (BD), color, and superoxide dismutase (SOD) activity of bayberry juice were investigated. Treatments were carried out at amplitude levels from 20 to 100% of total input power (600 W) at 20 kHz for 2–10 min. The results showed that no notable differences in pH, total soluble solids, titratable acidity, and yellowness b∗ values were found in ultrasound-treated samples. The HMF, PC, BD, and L∗ values of bayberry juice obviously increased with enhancing ultrasonic intensity and treatment time. The ascorbic acid exhibited no notable changes after ultrasound treatment at lower intensity levels for short time, while anthocyanins showed an increasing tendency. With increasing ultrasonic intensity and time, antioxidants gradually decreased. Furthermore, the SOD activity apparently increased at short-time treatment and then decreased with ultrasound processing extension.